Peran Lembaga Badan Amil Zakat Nasional (Baznas) Dalam Penyaluran Zakat Ditinjau Menurut Undang-Undang Nomor 23 Tahun 2011 Di Kabupaten Bengkalis - Ade Idra Suhara; J Juwandi (Universitas Islam Negeri Sumatera Utara, 2020)
This study discusses the role of the National Amil Zakat Agency (BAZNAS) in distributing Zakat in review according to Law Number 23 of 2011 in Bengkalis Regency. Particularly related to the distribution of Zakat which indicates the distribution of Zakat to the mustahik who are not on target. As well as inhibiting factors in the implementation of the role of the BAZNAS Intitution in the distribution of zakat in Bengkalis Regency. Zakat distribution which is distributed to Mustahik must be in accordance with Islamic shariah, the applicable regulations and also the Operational Standars in BAZNAS Bengkalis Regency. The nature of this study is qualitative with the type of Sociological Juridical. From the results of research on the Role of the Institution of BAZNAS in the Distribution of Zakat in Bengkalis Regency to the mustahik has been carried out optimally in accordance with existing operational standards, and of course in accordance with Islamic sharia and applicable regulations, but still must continue to make improvements, innovations, innovation to continue to improve the performance of Amil BAZNAS Bengkalis Regency. However, there are also several factors that hamper the role of BAZNAS institutions in the implementation of zakat distribution, namely in Human Resources (HR), limited operational funds, low public khowledge about Zakat, and lack of public trust in the goverment in dealing with zakat issues, especially the National Zakat Boards as an official goverment body.